Dartanan: Prototype evaluations of a serious game to engage children in the calibration of their hearing aid functionalities. (June 2021) - Hallewell, Madeline; Salanitri, Davide; D'Cruz, Mirabelle; Cobb, Sue; Picinali, Lorenzo; Frost, Emily; Tamascelli, Stefano; Patel, Harshada; ,
Introduction: It is notoriously difficult to obtain a perfect fitting of hearing aids (HAs) for children as they often struggle to understand their hearing loss well enough to discuss the fitting adequately with their audiologist. Dartanan is an 'edutainment' game developed to help children understand the functions of their HA in different sound contexts. Dartanan also has elements of a leisure game for all children, in order to create an inclusive activity. Methods: Game prototypes were evaluated during two formative evaluations and a summative evaluation. In total 106 children with and without hearing loss in Italy, Spain and the UK played Dartanan. A built-in virtual HA enabled children with hearing loss to use headphones to play. Results and conclusions: During the formative stages, feedback was discussed during focus groups on factors such as the audiological aspects, the extent to which children learned about HA functions, accessibility and usability, and this feedback was presented to the developers. After redevelopment, a summative evaluation was performed using an online survey. It was concluded that the game had met the goals of helping children understand their HA functionalities and providing an inclusive activity. User-evaluations were crucial in the development of the app into a useful and useable service.